Vitamin D Status and its Correlation with Disease Severity among Patients Presented with Major Depressive Disorders in a Tertiary Health Care Hospital in South India - Thekkuttuparambil A Ajith; Shiny John; S Achu (Universitas Padjadjaran, Indonesia, 2022)
Vitamin D level has a significant inverse correlation with depressive symptoms. The associa- tion of vitamin D level with unipolar or bipolar disorders are inconclusive among Indians. This study was aimed to find the severity of major depressive disorders and their correlation with vitamin D status. A cross-sectional study was conducted among patients (15-65 years old) diagnosed clinically with a major depressive disorder with a known serum 25 (OH) D levels. Mild, moderate, and severe depressive disorders were categorized into groups like vitamin D sufficient (≥75 nmol/L), insufficient (51-74 nmol/L), and deficient (<50 nmol/L). The data were analyzed for correlation. A total of 83 patients (33 males and 50 females) were included. Among the total, only four patients (4.8%) had bipolar disorder, while 79 patients (95.1%) had the unipolar disorder. Three bipolar patients and 68 unipolar patients had 25(OH)D levels below normal. Correlation analysis between the severity of disease and 25(OH)D level found a non-linear negative correlation in males (r= -0.07595, p= 0.7123) and positive correlation in females (r= 0.04234, p= 0.7823). However, correlation of age with 25(OH)D level was positive in males (r= 0.4151, p= 0.035) and negative in females (r= -0.1553, p= 0.3085). A negative correlation was found between the severity of the unipolar disorder and serum 25(OH)D levels in males. Therefore, male patients presented with the unipolar depressive disorder may consider vitamin D supplementation